Dakwah Kultural melalui Upacara Hari Besar Nasional di Pesantren YPP Nurul Islam Mojokerto - Setiawan Budi; Gusti Agung Cahyono; M. Ibda’u Shulhi; Sulistyowati (Universitas Islam Cordoba Banyuwangi, 2025)
This research is based on the fact that national holiday ceremonies in educational institutions are often viewed as mere formal rituals, whereas in Islamic boarding schools (pesantren) they have the potential to become spaces for the formation of national and religious character simultaneously. This study aims to describe and analyze national holiday ceremonies as a medium for cultural da'wah at the YPP Nurul Islam Islamic Boarding School in Mojokerto. The approach used is qualitative with a phenomenological design, through participatory observation, semi-structured interviews, and documentation studies, which are analyzed using the interactive model of Miles and Huberman with triangulation of sources and methods. The results of the study show that national holiday ceremonies at YPP Nurul Islam Mojokerto are always integrated with colossal dramas of local and national history, traditional dances, parades of traditional clothing, and national and regional songs as a medium for cultural da'wah. Through this series, the values ​​of love for the homeland, diversity, religious moderation, mutual cooperation, and respect for ancestral traditions are conveyed through symbols and cultural practices that are close to the lives of students, and are interpreted as practicing the teachings of hubbul wathan minal iman as well as learning about nationality. This study concludes that national ceremonies in Islamic boarding schools have great potential as an arena for cultural da'wah that integrates religion, state, and local wisdom in a creative and contextual manner.